Studi Perencanaan Perkerasan Kaku Menggunakan Metode AASHTO 1993 Pada Ruas Jalan Lingkar Tuban (STA 13+180 -STA 19+980) - Anggra Teguh Saputra; Ibnu Sholichin; Fithri Estikhamah (Racic : Rab Construction Research, 2025)
Jalan Lingkar Tuban is a national strategic route on the north coast of Java that serves as an alternative to overcome various obstacles. It is expected that this road can encourage the overall growth of the city, improve the convenience of vehicle accessibility, and encourage economic growth without causing congestion. To achieve this, good pavement is essential. Given the high traffic volume and overloading that will be travelled on the Tuban Ring Road, rigid pavement planning is highly recommended. The method used in this research is the AASHTO 1993 method, as it has been widely adopted by many countries abroad. The result of this research is 390 mm thick rigid pavement, 100 mm foundation layer (LMC), and 150 mm drainage layer.  The cost budget plan obtained results worth Rp 128,804,000,000 (One Hundred TwentyEight Billion Eight Hundred Four Million Rupiah).